SPEECH COMPOSING MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Jessica Djaja Putra; Mariska Budialim; Djunita Djunita; Michelle Yaputri Budiman (JCH (Jurnal Cendekia Hukum), 2019)
Speech Composing is a creation that has not been clearly regulated in Law Number 28 Year 2014 on Copyright. This opens up the possibility of copyright infringement from making Speech Composing. Copyright is an exclusive right of the creator granted by the State automatically after a creation is manifested in its tangible form. This exclusive right consists of the eternal inherent moral rights of the creator and the economic right of creation. Often people think just by putting the name of the creator in his work can prevent him from copyright infringement. Whereas the element of permission is an absolute thing if there are other parties who want to utilize the economic rights of the creator under Article 9 paragraph 2 of Law No. 28 of 2014 on Copyright. In this regard, X is the person who composed a song in Speech Composing using pieces of speech in AW's speech and uploaded to YouTube with no rights and without permission from AW. X infringes AW's copyright under Article 43 Sub-Article d of Law No. 28 of 2014 on Copyright.